Gene Therapy and CRISPR/Cas Technology in Dentistry: A Review - Arthi Marimuthu; Rathna P Subramani; Geeth Deepika; Azhagu A Alagianambi (Dental Journal of Advance Studies)
Background: The evolution of gene therapy, conceptualized in the 1960s, reached a pivotal moment in 1989–1990 with the approval of the first human clinical studies. Gene therapy, as defined by the US Food and Drug Administration (FDA), involves the administration of genetic material via nucleic acids, viruses, or genetically engineered microorganisms. This review explores the historical development and current landscape of gene therapy, focusing on its applications in dentistry. Materials and methods: A comprehensive narrative literature search, utilizing PubMed, MEDLINE, Scopus, and Web of Science databases, was conducted. Keywords and MeSH terms related to gene therapy, CRISPR/Cas technology, and dentistry were employed. Inclusion criteria encompassed English-language publications from the last 10 years, specifically focusing on the gene therapy or CRISPR/Cas applications in dentistry. Data synthesis involved critical appraisal and extraction of relevant information. Results: Gene transfer, a cornerstone of gene therapy, involves modifying defective genes through the injection of genetically modified vectors into target cells, either in vivo or ex vivo. Various methods, including physical (electroporation, microinjection) and chemical (calcium phosphate, liposome) approaches, facilitate gene modification. Dentistry applications range from addressing diseases such as squamous cell carcinoma and Sjogren's syndrome to enhancing bone regeneration, implants, and managing chronic pain. Conclusion: The potential of gene therapy and CRISPR/Cas technology in dentistry is vast, offering innovative, personalized therapeutic interventions. However, challenges such as ethical considerations and the need for long-term efficacy studies must be addressed to ensure the transformative impact of these technologies on oral healthcare practices. The future promises a paradigm shift in dental care, with gene therapy leading the way towards more effective and targeted treatments.